Usability Analysis of Anggavision Website as an Independent Learning Media for Videography Community - Angga Gumilang; Febri Liantoni (Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to measure and analyze the usability level of the Anggavision Website as an independent learning media for members of a videography community. The novelty of this research lies in evaluating the system usability of an independent learning platform specifically designed to support an extracurricular videography community, shifting the focus from measuring pedagogical learning outcomes in standard classroom settings to assessing UI/UX feasibility for novice students. A descriptive quantitative approach was employed. Initially, all 46 active members of the SMP Baitul Muttaqin Videography Community were involved through saturated sampling. To maintain data integrity and mitigate response bias, a strict data screening process was applied to eliminate 8 anomalous entries such as central tendency bias and straight lining resulting in 38 valid respondents. Data were collected using the standardized System Usability Scale (SUS) questionnaire, which had passed validation by media and material experts, and analyzed using the standard SUS calculation algorithm. The results showed that the Anggavision Website obtained an overall average SUS score of 73.35. Practically, this score signifies that the website possesses a solid ergonomic quality (Grade B) and highly intuitive navigation (Good), which successfully minimizes the cognitive load for beginner users. In conclusion, the Anggavision Website is proven to be highly usable, user friendly, and acceptable as a digital repository platform for extracurricular videography communities, without claiming pedagogical learning effectiveness.